Implementasi Website Booking Service Online untuk Meningkatkan Efisiensi Layanan Pada UMKM Bengkel Murni Jaya Benowo - Murnawan, Hery; Liwaq, Moch Isabil; Nisa, Saskia Choirul; Anggara, Agil Dwi; Ibrahim, Hilman Maulana; Riady, Narendra Raffee (Yayasan Cendekia Gagayunan Indonesia, 2025)
This community service program aims to support the digital transformation of the Murni Jaya Benowo automotive workshop by developing an online booking service website. The main issues faced by the UMKM include manual service booking, irregular scheduling, communication errors, and limited customer data documentation. The implementation method consisted of needs assessment, system design, website development, system installation, and training for the workshop owner. The results indicate that the developed website successfully provides online booking features, scheduling management, and an admin dashboard to streamline service operations. The training improved the owner's ability to operate the system independently, ensuring the sustainability of the digital solution. This digitalization initiative positively impacts operational efficiency, enhances service professionalism, and improves accessibility for customers. The program is expected to serve as a model for other UMKM to adopt digital technologies and strengthen competitiveness in the digital era.